Pengaruh Cedera terhadap Kecemasan Atlet Pencak Silat Satria Agung - Eva Supriaten; Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan)
Being an athlete is not easy, to achieve maximum results requires readiness starting from physical, technical, tactical readiness as well as mental readiness. The main factor that must be prepared by athletes is mental readiness. Mental readiness itself mainly includes anxiety, where anxiety can trigger an athlete's psychology. This study aims to determine whether there is an effect between injury on the anxiety of martial art satria agung athletes. The hypothesis in this study is that the higher / heavier an athlete has experienced, the higher the anxiety felt by an athlete, and vice versa, the lower or less severe the injury experienced by an athlete, the lower the anxiety felt by an athlete. The subjects of this study were 75 athletes. The collection was done by distributing two scales, namely the scale of anxiety and also the scale of injury. Based on the validity calculation, 28 valid items and 12 invalid items with a reliability correlation of 0.978 are obtained. In the injury scale, 29 valid items and 11 invalid items were obtained with a reliability correlation of 0.718. From the calculation results obtained Fcount 163.495 stated as significant because f count> from f table 1% is 5.29, It can be concluded that the hypothesis in this study is accepted.